1997
DOI: 10.1073/pnas.94.22.11893
|View full text |Cite
|
Sign up to set email alerts
|

Participation of the nuclear cap binding complex in pre-mRNA 3′ processing

Abstract: Communication between the 5 and 3 ends is a common feature of several aspects of eukaryotic mRNA metabolism. In the nucleus, the pre-mRNA 5 end is bound by the nuclear cap binding complex (CBC). This RNA-protein complex plays an active role in both splicing and RNA export. We provide evidence for participation of CBC in the processing of the 3 end of the message. Depletion of CBC from HeLa cell nuclear extract strongly reduced the endonucleolytic cleavage step of the cleavage and polyadenylation process. Cleav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
177
0
5

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(185 citation statements)
references
References 53 publications
3
177
0
5
Order By: Relevance
“…Polyadenylation requires in addition to CPSF, poly(A) polymerase, and the nuclear poly(A) binding protein 1 (PABPN1, previously called PAB II, for review, see Wahle and Rü egsegger, 1999). Other proteins involved in either transcription, such as the carboxy-terminal domain of RNA polymerase II, or capping (nuclear cap-binding complex) and splicing (U2AF65) have been shown to greatly enhance the efficiency of the first step of the reaction (Flaherty et al, 1997;Hirose and Manley, 1998;Millevoi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyadenylation requires in addition to CPSF, poly(A) polymerase, and the nuclear poly(A) binding protein 1 (PABPN1, previously called PAB II, for review, see Wahle and Rü egsegger, 1999). Other proteins involved in either transcription, such as the carboxy-terminal domain of RNA polymerase II, or capping (nuclear cap-binding complex) and splicing (U2AF65) have been shown to greatly enhance the efficiency of the first step of the reaction (Flaherty et al, 1997;Hirose and Manley, 1998;Millevoi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Polyadenylation requires in addition to CPSF, poly(A) polymerase, and the nuclear poly(A) binding protein 1 (PABPN1, previously called PAB II, for review, see Wahle and Rü egsegger, 1999). Other proteins involved in either transcription, such as the carboxy-terminal domain of RNA polymerase II, or capping (nuclear cap-binding complex) and splicing (U2AF65) have been shown to greatly enhance the efficiency of the first step of the reaction (Flaherty et al, 1997;Hirose and Manley, 1998;Millevoi et al, 2002).The mammalian cell nucleus is a highly structured and dynamic compartment. Many nuclear factors are localized in morphologically well-defined structural units that include the nucleolus and several "nuclear bodies," such as the Cajal body (Gall, 2000), and the promyelocytic leukemia body (Zhong et al, 2000).…”
mentioning
confidence: 99%
“…The nuclear cap binding complex, CBC, stimulates excision of the most 5Ј-located intron in vitro (Ohno et al 1987;Inoue et al 1989;Izaurralde et al 1994) and has been shown to facilitate U1 snRNP binding to the cap-proximal 5Ј-splice site (Lewis et al 1996). It has also been shown that CBC enhances endonucleolytic cleavage at the polyadenylation site (Flaherty et al 1997).…”
mentioning
confidence: 99%
“…(Figure 4). Toutefois, il existe encore peu de données susceptibles d'éclairer la relation entre la structure coiffe et le processus de maturation de l'extrémité 3' de l'ARN pré-m. Malgré tout, on constate bien une association entre le complexe CBP20-CBP80 et certains facteurs participant au clivage endonucléolytique [14]. Cette affinité a pour objectif premier d'augmenter l'efficacité du clivage par la stabilisation de CPSF et de CstF à l'ARN.…”
Section: Interactions Entre Les Processus De Maturation De L'arnmunclassified
“…Cette affinité a pour objectif premier d'augmenter l'efficacité du clivage par la stabilisation de CPSF et de CstF à l'ARN. On retrouve toutefois une influence positive sur l'élongation de la queue de poly(A) qui demeure modeste (Figure 4) [4,14]. En effet, la délétion du complexe CBP20-CBP80 a La position exacte de ce dernier site est déterminée par la distance existant entre l'hexanucléotide et la séquence riche en U ou en G/U.…”
Section: Interactions Entre Les Processus De Maturation De L'arnmunclassified